PENGGUNAAN MEDIA ISPRING dan POWER POINT PADA SUB KONSEP HUKUM - HUKUM DASAR KIMIA UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS X SMA NEGERI 7 AMBON - K Pooroe; F A Hamid; S Unwakoly (Jurusan Pendidikan MIPA FKIP Universitas Pattimura, 2020)
This study aims to determine the learning outcomes of students in X grade of SMA Negeri 7 Ambon, after using Ispring media and power points in learning process. The population of this research is all students of X grade, and the sample is X1 class consist of 17 students. Student learning outcomes data on sub concepts of chemical basic laws obtained through final tests, student worksheets (LKPD), affective assessment sheets, and psychomotor assessment sheets with the presentation of the results obtained by 1 student (5.88%) getting qualified very good, 5 students (35,29%) get good qualifications, 7 students (35,29%) get enough qualifications and 4 students (23.52%) with less qualifications. Learning outcomes show all students (100%) successfully reach the minimum completeness criteria (KKM) of 70